Blocking Complement Factor B Activation Reduces Renal Injury and Inflammation in a Rat Brain Death Model - Jager, Neeltina M.; van Zanden, Judith E.; Subías, Marta; Leuvenink, Henri G. D.; Daha, Mohamed R.; Rodríguez de Córdoba, Santiago; Poppelaars, Felix; Seelen, Marc A. (Frontiers in Immunology, 2019)
Introduction The majority of kidneys used for transplantation are retrieved from brain-dead organ donors. In brain death, the irreversible loss of brain functions results in hemodynamic instability, hormonal changes and immunological activation. Recently, brain death has been shown to cause activation of the complement system, which is adversely associated with renal allograft outcome in recipients. Modulation of the complement system in the brain-dead donor might be a promising strategy to improve organ quality before transplantation. This study investigated the effect of an inhibitory antibody against complement factor B on brain death-induced renal inflammation and injury. Method Brain death was induced in male Fischer rats by inflating a balloon catheter in the epidural space. Anti-factor B (anti-FB) or saline was administered intravenously 20 minutes before the induction of brain death (n=8/group). Sham-operated rats served as controls (n=4). After 4 hours of brain death, renal function, renal injury and inflammation were assessed. Results Pretreatment with anti-FB resulted in significantly less systemic and local complement activation than in saline-treated rats after brain death. Moreover, anti-FB treatment preserved renal function, reflected by significantly reduced serum creatinine levels compared to saline-treated rats after 4 hours of brain death. Furthermore, anti-FB significantly attenuated histological injury, as seen by reduced tubular injury scores, lower renal pro-inflammatory gene expression levels (>75%) and renal deposition of kidney injury marker-1. In addition, anti-FB treatment significantly prevented renal macrophage influx and reduced systemic IL-6 levels compared to saline-treated rats after brain death. Lastly, renal gene expression of IL-6, MCP-1 and VCAM-1 were significantly reduced in rats treated with anti-FB. Conclusion This study shows that donor pretreatment with anti-FB preserved renal function, reduced renal damage and inflammation prior to transplantation. Therefore, inhibition of factor B in organ donors might be a promising strategy to reduce brain death-induced renal injury and inflammation.